Plasma Aβ in cerebral microbleeds‐positive subjects with cognitive impairment: Biomarkers (non‐neuroimaging) / Differential diagnosis. (7th December 2020) - Liu, Shan; Ito, Hitomi; Ogawa, Norihiro; Akatsu, Hiroyasu; Uchida, Kazuhiko
Abstract: Background: Cerebral amyloid angiopathy (CAA) is strongly related to Alzheimer's disease (AD). Accumulation of amyloid affects pathophysiology of parenchyma and vessels in amyloidosis. Continuum of amyloid pathology may result in complicated clinical symptoms due to overlap of vascular and neurodegenerative factors during amyloidosis. MRI can detect hemosiderin deposits as cerebral microbleeds (CMBs) and cortical superficial siderosis. CMBs may be involved in amyloid pathology in AD and mixed dementia. Here, we analyzed relationship of these cerebrovascular changes to plasma Aβ42 and Aβ40 levels. Method: Age‐matched subjects with cognitive impairment were classified into CMBs‐positive, ‐suspective and ‐negative groups by MRI. Plasma Aβ42, Aβ40, BACE1 levels were determined by ELISA (ADx, Euroimun). Result: There is no significant changes of MMSE score and hippocampal atrophy among the CMBs groups. CMBs‐positive subjects showed lower Aβ42 levels and higher Aβ40/42 ratio in plasma. Plasma BACE1 levels showed no significant change in CMBs‐positive subjects. Conclusion: CMBs, plasma Aβ42 and Aβ40/42 ratio may be potential biomarkers for amyloid pathology in cognitive impairment.